GAMBARAN TINGKAT KECEMASAN ORANG DENGAN HIV/AIDS (ODHA) PADA KELOMPOK DUKUNGAN SEBAYA ARJUNA (KDSA) DI KOTA SEMARANG - Argenis, Gergoria; Anastasia Diah Larasati; Nila Titis Asrining Tyas (Jurnal Perawat Indonesia, 2021)
Severe acute respiratory syndromecoronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. The disease caused by this viral infection is called COVID-19. COVID-19 can attack anyone, one of them is people living with HIV/AIDS (PLWHA). One of the consequences of the COVID-19 pandemic for PLWHA is anxiety. Ongoing anxiety problems result in PLWHA being irregular in taking treatment, and difficulties in obtaining health facilities. This research is a quantitative-research that is descriptive analytic. The sampling technique used is simple random sampling with a total sample of 45 respondents. Data is presented in the form of tables, pictures, and narratives. Respondents with no anxiety category 17 (37.8%), mild anxiety 15 (33.3%), moderate anxiety 10 (22.2%), severe anxiety 3 (6.7%). Based on gender, male respondents who were not anxious 8 (17.8%), mild anxiety 12 (26.7%), moderate anxiety 6 (13.3%), severe anxiety 3 (6.7%), female who are not anxious are 9 (20.0%), mild anxiety 3 (6.7%), moderate anxiety 4 (8.8%), severe anxiety 0 (0.0%). Based on age, respondents with no anxiety were 13 (28.9%), mild anxiety 13 (28.9%), moderate anxiety 9 (20.0%), severe anxiety 3 (6.7%). In the middle age, respondents who were not anxious were 4 (8.9%), mild anxiety 2 (4.4%), moderate anxiety 1 (2.2%), and severe anxiety 0 (0.0%). Most of the respondents did not experience anxiety as many as 17 respondents (37.8%). Male respondents were dominant in mild anxiety, namely 12 (26.7%) while women in the non-anxious category were 9 (20.0%). Adult respondents in the non-anxiety and mild anxiety categories were 13 respondents (28.9%), while middle age dominated the non-anxious category, namely 4 respondents (8.9%). So, the level of anxiety between one respondent and another respondent will be different, this is because one of the factors is age, and gender.